Urban Flood Management Strategies in Kapanewon Depok, Sleman Regency (A Simulation-Based Study Using EPA SWMM 5.2) - Sawitri, Nurin Retno; Christanto, Nugroho; Retnowati, Arry (The Indonesian Journal of Planning and Development, 2025)
Kapanewon Depok has experienced frequent urban flooding in recent years, driven by rapid urbanization and the compounding effects of climate change. In response, the Sleman Regency Government, through the 2023-2043 RDTR for the Central Sleman Area, plans to implement various strategies, including the construction infiltration trenches as a flood mitigation strategy. This study aims to evaluate the strategic role and effectiveness of infiltration trenches in reducing urban flooding in Kapanewon Depok. The EPA SWMM 5.2 software was utilized to simulate urban flooding scenarios using rainfall data with a 5-year return period. The first scenario simulated the current urban drainage system, while the second scenario incorporated Low-Impact Development (LID) controls, specifically infiltration trenches. Results from the initial scenario revealed 30 junctions experiencing overflows. The use of infiltration trenches covering 0.5% of the sub-catchment area served by the overflowing channel, successfully reduced the number of overflow points to 18, with an average reduction of 62.5% and 62% total flood volume and hours flooded, respectively. This study highlights the importance of integrating infiltration trenches into broader flood management strategies, combining structural and non-structural approaches to enhance resilience in urban water management systems. The findings support regional planning by providing actionable recommendations for sustainable flood risk reduction strategies.